Model peptides mimic the structure and function of the N-terminus of the pore-forming toxin sticholysin II - Casallanovo, F.; de Oliveira, FJF; de Souza, F. C.; Ros, U.; Martinez, Y.; Penton, D.; Tejuca, M.; Martinez, D.; Pazos, F.; Pertinhez, T. A.; Spisni, A.; Cilli, Eduardo Maffud [UNESP]; et al. (Wiley-Blackwell, 2006)
To investigate the role of the N-terminal region in the lytic mechanism of the pore-forming toxin sticholysin II (St II), we studied the conformational and functional properties of peptides encompassing the first 30 residues of the protein. Peptides containing residues 1-30 (P1-30) and 11-30 (P11-30) were synthesized and their conformational properties were examined in aqueous solution as a function of peptide concentration, pH, ionic strength, and addition of the secondary structure-inducing solvent trifluoroethanol (TFE). CD spectra showed that increasing concentration, pH, and ionic strength led to aggregation of P1-30; as a consequence, the peptide acquired beta-sheet conformation. In contrast, P11-30 exhibited practically no conformational changes under the same conditions, remaining essentially structureless. Moreover, this peptide did not undergo aggregation. These differences clearly point to the modulating effect of the first 10 hydrophobic residues on the peptides aggregation and conformational properties. In TFE both the first ten hydrophobic peptides acquired alpha-helical conformation, albeit to a different extent, P11-30 displayed lower alpha-helical content. P1-30 presented a larger-fraction of residues in alpha-helical conformation in TFE than that found in St II's crystal structure for that portion of the protein. Since TFE mimics the membrane em,, such increase in helical content could also occur upon toxin binding to membranes and represent a step in the mechanism of pore formation. The peptides conformational properties correlated well with their functional behaviour. Thus, P1-30 exhibited much higher hemolytic activity than P11-30. In addition, P11-30 was able to block the toxin's hemolytic activity. The size of pores formed in red blood cells by P 1-30 was estimated by measuring the permeability PEGs of different molecular mass. The pore radius (0.95 +/- 0.01 nm) was very similar to that of the PEGs of different pore formed by the toxin. The results demonstrate that the synthetic peptide P1-30 is a good model of St 11 conformation and function and emphasize the contribution of the toxin's N-terminal region, and, in particular, the hydrophobic residues 1-10 to pore formation. (c) 2005 Wiley Periodicals, Inc.
Keywords: Sticholysin II; Actinoporin; Pore-forming toxin; Hemolytic peptide; Circular dichroism